If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 2x + -15 Reorder the terms: 3y = -15 + 2x Solving 3y = -15 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = -5 + 0.6666666667x Simplifying y = -5 + 0.6666666667x
| y=x^2-8x+195 | | (2x^2+6x-3)+(2x^3-3x+2)= | | 3x+2=-3x+20 | | 2x+8=3x*x+4 | | -9-x=6x-79 | | -5x+11x-49=77 | | 2x+3+y+2=180 | | (r-3s+t)(2r-s+t)=0 | | 6y=4-1.69 | | 24=3(n+15) | | 3x+2=-3+20 | | 2(4y-5x)=6y-20 | | 9=4c-11 | | 18372747267284717839274728726472+98377778777777293771898472984727384774918999999999999999917373892946584456673485753756427426427538673=1 | | 2[4+2(5-x)-2x]=4(7+2x) | | -7x-2+x=-62 | | =(2x^3-7x^2+7x)+(2x^3+9x^2-14x) | | 5(2n+5)=6(8n+6)+5 | | 8x-3-3x=5x | | 35=8x-53 | | 2x+22=4x+4 | | (3x+5)+(2x-7)+x=180 | | 123456789+123456789=1 | | -7(n+4)+29=-4n-5 | | 49x^2+70x-11=0 | | (x+2)(12x^3-3x^2+x+1)=0 | | 19-34=-5x | | y^2+3y=54 | | 9999999999+9999999999=99999999999999999999 | | -15+x=x-17 | | (2x+1)(4x^2-2x+1)=0 | | 2x+3x+x+4x=180 |